Problem przynależności państwowej Vorarlberga po I wojnie światowej - Jeziorny, Dariusz (Acta Universitatis Lodziensis. Folia Historica, 2002)
Vorarlberg was a small (2600 km2 i 144 000 inhabitants), most Western land of Austria-Hungary. After the breakup of the Habsburg Monarchy the population of Vorarlberg tended to join Swiss Confederation. Incorporation into wealthier neighbour state was regarded as a possibility to avoid postwar extreme poverty that threatened German Austria. The inclination towards unification with Switzerland grew and achieved its top in May 1919, when the plebiscite was organised. 80% of people voted for joining the Swiss Confederation. The Swiss government (Federal Council) was very reserved towards the Vorarlberger’s steps. They did not say „no” because they were afraid of incorporation that land into Germany. It must be stated clearly th at the German influence and propaganda in Vorarlberg grew. Berlin knew the Entente will forbid the Anschluss of whole Austria but did not expect any problem in incorporation of a small land. It was very important strategical point of Europe. The Auswärtiges Amt regarded it as "a key to Austria". Its incorporation to Germany would threaten the Swiss strategical position and take back very large part of Swiss income that was received from railway payments (France would not be interested to use the Swiss railways in communication with the East if the ommiting of German ones would not be possible after the annexation of Vorarlberg). The Federal Coucil was also affraid of national ideas, namely uniting all Germans in one country. But the Bern government did not say „yes” as well. They regarded the internationally recogniscd neutrality as a priority. And the neutrality was concerned with the strictly determined borders. The Federal Council did not want to lose of neutral status connected with the change the Swiss territory. They also would not want to pay reparation forced on Vorarlberg. The change of national and denominational ballance was vigorously discussed too. But basically the Federal Council did not want to weaken Austria, because such steps could force her to join Germany. All those reasons decided that the Swiss government waited and delay all declarations connected with Vorarlbergers’ will. In such circumstances the Peace Conference in Paris maintained Vorarlberg as a part of the Austrian Republic.